1998
DOI: 10.1002/(sici)1097-4652(199809)176:3<648::aid-jcp22>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I-mediated survival from Anoikis: Role of cell aggregation and focal adhesion kinase

Abstract: Anoikis is a form of cell death that occurs when cells are denied attachment to the extra-cellular matrix. Using p6 cells, that are 3T3 cells overexpressing the type 1 insulin-like growth factor receptor (IGF-IR), we show that these cells undergo apoptosis when seeded on polyHEMA plates in serum-free medium (SFM). IGF-I protects p6 cells from anoikis, without inducing mitogenesis or DNA synthesis. In the surviving p6 cells in suspension cultures, the focal adhesion kinase (FAK) is tyrosyl phosphorylated by IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…It was reported a few years ago that normal cells deprived of matrix attachment undergo programmed cell death, termed anoikis (reviewed in Ruoslahti and Reed [1994]). Although first demonstrated in epithelial and endothelial cells (Frisch and Francis, 1994;Re et al, 1994), anoikis has now been observed to varying extents in a number of cell types, including smooth muscle and neuronal cells as well as various fibroblastic cells (Ishizaki et al, 1995;McGill et al, 1997;Meredith and Schwartz, 1997;Valentinis et al, 1998Valentinis et al, , 1999, and is reviewed in Meredith and Schwartz (1997). One biologically significant consequence of this phenomenon may be suppression of tumorogenesis, because the loss of anchorage dependence is one of the best correlates of tumoral growth in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported a few years ago that normal cells deprived of matrix attachment undergo programmed cell death, termed anoikis (reviewed in Ruoslahti and Reed [1994]). Although first demonstrated in epithelial and endothelial cells (Frisch and Francis, 1994;Re et al, 1994), anoikis has now been observed to varying extents in a number of cell types, including smooth muscle and neuronal cells as well as various fibroblastic cells (Ishizaki et al, 1995;McGill et al, 1997;Meredith and Schwartz, 1997;Valentinis et al, 1998Valentinis et al, , 1999, and is reviewed in Meredith and Schwartz (1997). One biologically significant consequence of this phenomenon may be suppression of tumorogenesis, because the loss of anchorage dependence is one of the best correlates of tumoral growth in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It does so in the absence of cell division. Hence, the mitogenic activity of IGF-I may be distinct from its survival activity as previously suggested (21)(22)(23).…”
Section: Discussionmentioning
confidence: 81%
“…Data from JCV T antigen-positive and -negative murine medulloblastoma cell lines (Krynska et al, 2000;Wang et al, 2001) indicate that the activation of mitogenic and antiapoptotic signals from the IGF-IR are modulated by the presence of JCV T antigen ( Figure 2). To deny attachment, cells were cultured on 35-mm dishes covered with polyHEMA as previously described Valentinis et al, 1998). In suspension, JCV T antigen-positive cells (BsB8) survive well in serum-free medium.…”
Section: Igf-ir In Medulloblastomasmentioning
confidence: 99%
“…JCV T antigen-positive (BsB8) cells, T antigen-negative (Bs-1a) cells, and Bs-1a cells stably transfected with JCV T antigen cDNA (pCDNA-3/zeo/JCV-T), Bs-1a/JCT cells, were cultured on PolyHema-coated plates to avoid cell attachment (Valentinis et al, 1998). The cells were cultured either in serum-free medium (SFM) or were stimulated with 50 ng/ml IGF-I (IGF).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation